Field Evaluation of the Interferon Gamma Assay for Diagnosis of Tuberculosis in Water Buffalo (Bubalus bubalis) Comparing Four Interpretative Criteria - Martucciello, Alessandra; Vitale, Nicoletta; Mazzone, Piera; Dondo, Alessandro; Archetti, Ivonne; Chiavacci, Laura; Cerrone, Anna; Gamberale, Fabrizio; Schiavo, Lorena; Pacciarini, Maria Lodovica; Boniotti, Maria Beatrice; De Carlo, Esterina (Frontiers in Veterinary Science, 2020)
Bovine tuberculosis (bTB) is a worldwide zoonosis that affects many species of domestic and wild animals. Mycobaterium bovis is the main cause of infection in water buffalo (Bubalus bubalis) and bovines and is of great concern for human health and for buffalo producers in Italy. The bTB eradication programme is based on slaughterhouse surveillance and intradermal skin tests. Other in vivo diagnostic methods such as the interferon-gamma (IFN-γ) assay have been developed and are widely used in cattle to accelerate the elimination of bTB positive animals. The present study is the first to assess the use and performance of IFN-γ assays, which is used as an ancillary test for bTB diagnosis in water buffalo, and presents the results of a field-evaluation of the assay from 2012 to 2019 during the buffalo bTB eradication programme in Italy. The study involved 489 buffaloes with a positive result to the single intradermal tuberculin test (SITT). The IFN-γ assays and single intradermal comparative tuberculin test (SICTT) were used as confirmation tests. Then, a total of 458 buffaloes, reared on officially tuberculosis-free (OTF) herds, that were confirmed bTB-free for at least the last 6 years were subjected to IFN-γ testing. Furthermore, to evaluate the IFN-γ test in an OTF herd with Paratuberculosis infection, 103 buffaloes were subjected to SITT and IFN-γ test simultaneously. Four interpretative criteria were used, and the IFN-γ test showed high levels of accuracy, with sensitivity levels between 75.3% (CI95% 71.2%-79.0%) and 98.4% (95CI% 96.7%-99.4%) and specificity levels between 94.3% (CI95% 91.2% - 96.50%) and 98.5% (CI95% 96.9%-99.4%), depending on the criterion used. Finally, in the OTF herd with Paratuberculosis infection, in buffalo, the IFN-γ test displayed high specificity values according to all 4 interpretative criteria, with specificity levels between 96.7% (CI95% 88.4% - 99.5%) and 100% (CI95% 96.2% - 100%), while SITT specificity proved unsatisfactory, with a level of 45.3% (CI95% 35.0-55.7%). The IFN-γ test and the use of different interpretative criteria proved to be useful to implement bTB diagnostic strategies in buffalo herds, with the possibility of a flexible use of the assay on the basis of different epidemiological conditions.